The role of effective communication in enhancing leadership skills among students of Bachelor of Management Mathematics in UiTM Perlis / Nur Fatin Amira Anuar - Anuar, Nur Fatin Amira (2021)
Communication is the most important key factor for a student to lead effectively, because it helps them to express their opinion. Some students are struggling to socialise with other students due to lack of communication skills. It is important for students to have effective communication because it helps them develop their leadership skills and can also improvise on their self-confidence. The purpose of this study were to identify the level of effective listening, performing tasks completely and effectively, clarity of thought and expression and leadership skills, to assess the significant difference of demographic variables (gender, age and semester) on effective listening, performing tasks completely and effectively, clarity of thought and expression and leadership skills, to determine the relationship between effective listening, performing tasks completely and effectively, clarity of thought and expression and leadership skills, and lastly to examine whether effective listening, performing tasks completely and effectively, clarity of thought and expression relate toward leadership skills. The random sample of 155 respondents is from Faculty of Computer and Mathematical Science (FSKM) at UiTM Perlis. In order to achieve all the objectives, the researcher has chosen to apply the frequency test, the independent t-Test, the one-way ANOVA, the correlation and regression performed by the Statistical Package for Social Sciences Version 20.0. (SPSS). Based on the findings, there is a positive relationship between the role of effective communication and leadership skills, but a great deal of determination is still needed to establish leadership criteria among undergraduates, as a few students have not been aware of the importance of leadership skills in their future careers. Moreover, the analysis shows that clarity of thought and expression are the most important roles that contribute to leadership skills. The role of effective communication in enhancing leadership skills among university students must be properly studied so that students can develop their ability to soon become a major leader